To agree or not to agree? consensus and performance in new ventures - West, G.Page; Meyer, G.Dale (Journal of Business Venturing, 1998)
It is an intuitively appealing notion that enhanced firm performance is associated with agreement by top managers on a fundamental set of strategic goals and on methods to accomplish those goals. Nowhere should this relationship be more pronounced than in new ventures. New ventures tend to focus on narrow sets of products or markets; therefore the range of conceivable goals and methods should be narrower than would be the case if these firms were competing with many products in diverse markets. In addition, younger companies suffer from a “liability of newness,” and lack the accumulated resources which allow more established firms to weather rough times. These conditions place an even higher premium on the need for top management of new ventures to agree on doing a few things very well. Previous research has evaluated the relationship between performance and top management consensus. Interestingly, the results have been mixed and have sometimes contradicted intuition that top management agreement is related to better performance. Whereas previous studies have for the most part examined this relationship in larger companies competing in stable industries, the study reported here provides findings from newer entrepreneurial ventures in dynamic industries. Several important findings emerge from this study. First, managers’ assessment of better performance is not related to agreement on a primary set of strategic goals and means. Instead, perceived better performance is significantly and positively related to disagreement on secondary sets of strategic goals and means.11In this study, primary goals and means are defined as those believed by the CEO to be of greater importance, and secondary goals and means are those believed by the CEO to be of lesser importance. See Methodology section for a specific description. Second, powerful individuals in top management teams have an important impact on the nature of the consensus-performance relationship. In new ventures the influence of the CEO’s perspective and behaviors in forging agreement cannot be overlooked. Third, these results are evident during the earlier life cycle stages of a venture’s development, and in dynamically changing competitive environments. The findings of this study have implications for new ventures and the venture capital firms which support them, and for established corporations seeking to become more entrepreneurial. Entrepreneurship may be viewed as thriving in a world of ideas. This study shows a strong correlation between perceptions of superior performance and the presence of idea diversity within top management teams. The importance of idea diversity in earlier stages of a venture’s development is especially interesting and contrasts with the traditional view of new ventures as being highly dependent on adherence to the founder CEO’s initiating vision. The relationships studied here also provide prescriptive advice for new ventures. Gaining agreement on all strategic issues by all top managers is not productive. Superior performance is not associated with this level of complete agreement. Attempting to force consensus among all managers on all issues may prevent important new ideas from being considered. In addition, we surmise that valuable firm resources may be used up in attempting to gain agreement across such a broad spectrum of strategic goals and means; their use in this manner may detract from their application toward other more substantive organizational issues. Both entrepreneurial firms as well as established companies seeking to become more entrepreneurial should find ways to encourage the generation of idea diversity, particularly in the incipient stages of their new ventures. For established firms simply flattening a corporate hierarchy to create more of an entrepreneurial type of organizational structure may not be sufficient. In this research some of the younger ventures, which presumably enjoyed the benefits of such structure, did not enjoy the benefits of broad idea diversity and performed less well. In established companies the presence of “corpocracy” may still overshadow and constrain both initiating vision and the subsequent generation of multiple perspectives affecting new ventures. These firms should seek to develop and improve organizational communication systems to enhance the production and flow of new ideas. The generation of idea diversity within start-up companies is particularly challenging. Often founder CEOs have technical backgrounds, but lack managerial experience. They may thus have difficulty in managing professionals in top management teams to generate diversity, and adherence to their initiating visions may also block consideration of other ideas. We suggest that firms therefore consider two alternatives to assist in the generation of multiple, challenging perspectives within the top management team. First, consideration might be given to hiring top managers with different industry and company backgrounds and who have not worked together previously. In addition, hiring practices might consider more subtle measures of managerial diversity, such as future time orientation or other cognitive dimensions such as integrative complexity. Second, new ventures might consider alternatives to traditional organization by function. This may include the creation of a position solely responsible for managing planning and developing idea diversity within the top management group. Firms might also consider rotating functional assignments among top managers in order to broaden each manager’s perspective.